2015
DOI: 10.17957/ijab/15.0052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on Na Accumulation, Antioxidant Enzyme Activities and Activity of Cell Wall Peroxidase of Huckleberry (Solanum scabrum) and Eggplant (Solanum melongena)

Abstract: To cite this paper: Assaha, D.V.M., L. Liu, A.M.M. Mekawy, A. Ueda, T. Nagaoka and H. Saneoka, 2015. Effect of salt stress on Na accumulation, antioxidant enzyme activities and activity of cell wall peroxidase of huckleberry (Solanum scabrum) and eggplant (Solanum melongena AbstractUnderstanding the adaptive mechanisms to salinity stress is an important prerequisite for crop improvement and sustainable production. The objective of this study was to compare the adaptation of huckleberry and eggplant to salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The plant root systems can respond to sodium chloride toxicity by changing structure, such as reducing root length (Mahajan and Tuteja 2005). Previous studies have shown that cell‐wall peroxidase activity and H 2 O 2 levels increased by sodium salt stress, while exogenous H 2 O 2 and peroxidase inhibited plant root growth (Marius Assaha et al 2015). When the temperature is lower than 25/15°C, the salinity has a significant effect on the root length, and the temperature has little effect on it.…”
Section: Discussionmentioning
confidence: 99%
“…The plant root systems can respond to sodium chloride toxicity by changing structure, such as reducing root length (Mahajan and Tuteja 2005). Previous studies have shown that cell‐wall peroxidase activity and H 2 O 2 levels increased by sodium salt stress, while exogenous H 2 O 2 and peroxidase inhibited plant root growth (Marius Assaha et al 2015). When the temperature is lower than 25/15°C, the salinity has a significant effect on the root length, and the temperature has little effect on it.…”
Section: Discussionmentioning
confidence: 99%
“…The malondialdehyde (MDA) concentration in the leaf blades and roots was determined as described in Assaha et al [13]. Fresh leaf blades and roots (100 mg) were homogenized in 6 mL of an extraction buffer (10 mM HEPES, pH 7, 15% trichloroacetic acid (TCA), 0.375% thiobarbituric acid, 0.25 N HCl, 0.04% butylated hydroxyl toluene (BHT), and 2% ethanol (EtOH), and heated at 95 • C for 30 min.…”
Section: Measurement Of Lipid Peroxidation (Mda)mentioning
confidence: 99%
“…When MDA levels are low, the plant metabolism is strong, which is conducive to accumulating assimilation products. Marius et al (2015) showed that MDA accumulation is inversely proportional to the protective ability of plant tissues within a specific range. Our results showed that the MDA content of the soybean leaves decreased significantly after being sprayed with DPC.…”
Section: Discussionmentioning
confidence: 99%